PENGARUH HIPERKOAGULASI TERHADAP MORTALITAS ASTROSITOMA PADA PEMANTAUAN 12 BULAN - Among Wibowo,* Tiara Aninditha,** Henry Riyanto Sofyan,** Rini Andriani*** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION ASTROCYTOMA IS THE MOST COMMON PRIMARY BRAIN TUMOR HYPERCOAGULABLE STATE IS ONE OF BRAIN TUMOR COMPLICATIONS WHICH CAN CAUSE VEIN THROMBOEMBOLISM VTE VEIN THROMBOEMBOLISM INCIDENCE IS INCREASED IN ASTROCYTOMA PATIENTS HYPERCOAGULABLE STATE IN ASTROCYTOMA COULD LOWER PATIENTS SURVIVAL